DETERMINASI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ni Putu Monyati; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Dividend policy is a financial decision made by a company after the company operates and earns a profit. This policy concerns whether the profits earned by the company will be distributed to shareholders as dividends or withheld for future investment financing. The purpose of this study was to determine the effect of liquidity, company size and growth partially and simultaneously on dividend policy. This research was conducted in manufacturing companies on the Indonesia Stock Exchange for the 2015-2018 period. The sample in this study were 39 companies obtained through purposive sampling method and studied for 4 years so that in this study as many as 156 samples. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that liquidity has a negative effect on dividend policy, company size is negative on dividend policy, and growth has a positive effect on dividend policy.